New and little known species of the genus Martiodrilus Michaelsen, 1936 from French Guiana (Oligochaeta, Glossoscolecidae) - Csuzdi, Csaba; Pavlíček, Tomáš (Zootaxa, 2011)
The genus Martiodrilus is native to South America, with two species, Martiodrilus tenkatei (Horst, 1887) and Martiodrilus duodenarius (Michaelsen, 1918), previously recorded from French Guiana. In this paper we verified the presence of both species in French Guiana and provided a new record, Martiodrilus (Botaria) helleri (Michaelsen, 1918). Furthermore, two new species were described: Martiodrilus (Botaria) dewynteri sp. nov. and Martiodrilus (Maipure) gaucheri sp. nov. The subgeneric division of the genus Martiodrilus is briefly discussed.